Student Voice Key to Unlocking Inclusive Educational Practices - Maria Gordon (Canadian Society for Studies in Education, 2010)
A review of the educational policies and procedures in Canada's provinces and territories reveals that inclusion of students with disabilities in regular classrooms is the dominant policy (Hutchinson, 2007). However, inclusive education was also shown to vary in the ways it was implemented throughout Canada. Therefore, there appears to be a 'gap' between the concept of inclusive education and that which is actually practiced in schools. The background literature from students' perspective has been limited. Thus, this paper presents the argument that in order to comprehend the efficacy of inclusion it is important to conduct research from the student's perspective since they are the recipients and participants of inclusive educational practices.